2013
DOI: 10.2166/wst.2013.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oil–mineral aggregation with modified bentonite

Abstract: The application of modified-bentonite-enhanced oil dispersion in water and oil-mineral aggregate (OMA) formation was studied in the laboratory. The effect of modification on the surface properties of bentonite was characterized. The hydrophobicity and surface electric properties of bentonite were significantly improved by attaching cetyltrimethyl ammonium bromide to its surface. The results showed that surface properties of bentonite played an important role in OMA formation. Spherical droplets of OMAs were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The abundant chemically dispersed oil droplets, with a smaller size and larger surface area, might sufficiently interact with quartz sand of several micron scales. Considering the hydrophobicity of sediment particles, the addition of a chemical dispersant could enhance the surface hydrophobicity of quartz sand, leading to the improvement in the formation of OSAs [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…The abundant chemically dispersed oil droplets, with a smaller size and larger surface area, might sufficiently interact with quartz sand of several micron scales. Considering the hydrophobicity of sediment particles, the addition of a chemical dispersant could enhance the surface hydrophobicity of quartz sand, leading to the improvement in the formation of OSAs [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Clays are more effective than other minerals, such as quartz, in part because of they have higher surface area (Omotoso et al, ; Zhang et al, ). Additionally, hydrophobic minerals have a greater tendency to form OPAs than hydrophilic minerals, and researchers have recently shown that the effectiveness of traditional minerals, such as bentonite and kaolinite, can be enhanced by altering their natural surface properties to increase their hydrophobicity (Chen et al, ; Lee et al, ; Wang et al, ; Zhang et al, ). Zhang et al () also explored the effectiveness of materials that would not typically be found in a beach environment, such as fly ash and graphite, but had limited success compared to traditional minerals.…”
Section: Formationmentioning
confidence: 99%
“…Several investigations were carried out to understand the various mechanisms involving the formation of aggregates  generally termed Oil Particle Aggregates (OPAs) ,  when oil interacts with suspended particles (including both organic and inorganic matter , ), whereby it was observed that such aggregation processes are mainly caused by the hydrophobic adsorption between the sediments and the crude oil’s polar compounds (i.e., asphaltenes and resins). Therefore, crude oils with a relatively high fraction of polar compounds are more inclined to form OPAs, and hydrophobic sediments, such as bentonite and kaolinite, are mostly investigated. ,− …”
Section: Introductionmentioning
confidence: 99%